Differences in attentional functioning between preterm and full‐term children underline the importance of new neuropsychological detection techniques. (1st February 2017) - Giordano, V; Fuiko, R; Leiss, U; Brandstetter, S; Hayde, M; Bartha‐Doering, E; Klebermaß‐Schrehof, K; Weiler, LJ
Abstract: Aim: The aim of this study was to investigate specific attentional components in preterm born children who had not yet started school. Methods: Between January and December 2011, we assessed 52 preterm and 52 full‐term children aged between five years five months and six years two months, of comparable age and gender, at the Medical University of Vienna. Different attentional components were evaluated through selected subtests of the Test of Attentional Performance and the German version of the Wechsler Intelligence Scale for Children. Each child's behaviour was also evaluated using parental ratings and descriptive item‐based evaluation during neuropsychological assessment. Results: Children born preterm showed poor attentional performance in sustained attention, focused attention and distractibility, as well as reductions in processing speed in divided attention and flexibility tasks. Children born preterm also showed decreased volitional attention compared with automatic attention. No problems were detected in alertness or inhibition. In addition, a higher rate of aborted tests, decreased motivation and poorer parental ratings were detected among the preterm population compared with full‐term born children. Conclusion: Our results highlighted differences in attentional functioning between preterm and full‐term children, indicating the importance of new neuropsychological techniques for the detection of specific attentional disorders.